METTL14 in tumor immunity: epitranscriptomic regulation and therapeutic potential - Li, Chunhong; Jiang, Xiulin; Yuan, Yixiao; Wang, Qiang (Frontiers in Immunology, 2025)
N6-methyladenosine (m6A) is the most abundant internal RNA modification, orchestrated by writers, erasers, and readers. METTL14, a key component of the m6A methyltransferase complex, acts as a structural scaffold that ensures substrate recognition and modification precision. Beyond this canonical role, METTL14 regulates multiple biological processes, including chromatin remodeling, transcriptional activity, and senescence-associated signaling. Recent studies highlight its pivotal function in tumor immunity: METTL14 shapes T cell differentiation, CD8+ T cell activation, and the activity of macrophages and NK cells, thereby remodeling the tumor immune microenvironment. Moreover, METTL14 directly modulates immune checkpoint pathways by regulating PD-1 and PD-L1 expression, linking epitranscriptomic control with immune escape and therapeutic resistance. Aberrant METTL14 expression correlates with tumor progression and immune evasion, underscoring its potential as a predictive biomarker and therapeutic target. Targeting METTL14, alone or in combination with immune checkpoint inhibitors, may provide novel strategies to enhance immunotherapy efficacy.